2013
DOI: 10.1097/dbp.0000000000000010
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Imposed Sedentary Behavior and Exercise on Energy Intake in Adolescents With Obesity

Abstract: Whereas intense exercise reduces daily energy balance in adolescents with obesity by mainly affecting ad libitum dinner energy consumption, imposed sedentary behaviors lead to increased energy intake and then positive energy balance. The impact of exercise or imposed sedentary behaviors on the energy balance of adolescents with obesity is not only related to the exercise-induced energy expenditure, but also to their energy intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…This absence of post-exercise modification of the EI derived from each macronutrient remains difficult to interpret due to limited and contradictive results in this population [11,18,27,28]. Our results regarding appetite feelings confirm once more the previously described “uncoupling effect” of acute exercise on appetite sensations and EI [29], since hunger, satiety or prospective food consumption were not modified by exercise in either lean or obese adolescents.…”
Section: Discussionsupporting
confidence: 49%
“…This absence of post-exercise modification of the EI derived from each macronutrient remains difficult to interpret due to limited and contradictive results in this population [11,18,27,28]. Our results regarding appetite feelings confirm once more the previously described “uncoupling effect” of acute exercise on appetite sensations and EI [29], since hunger, satiety or prospective food consumption were not modified by exercise in either lean or obese adolescents.…”
Section: Discussionsupporting
confidence: 49%
“…Indeed, when considering obese children and adolescents separately, the results are much more ambiguous, with one study showing increased intake (8), 5 showing a decrease (9,(24)(25)(26)31), and 7 showing no difference (8,25,26,(28)(29)(30). Although our meta-analysis approaches found no significant 325 effect of acute exercise in lean youth, it shows significantly reduced post-exercise food ingestion in obese ( Figure 2B).…”
Section: Discussionmentioning
confidence: 60%
“…However, the systematic review indicated that children and adolescents do not alter the macronutrient composition of their meal in response to acute exercise (9, 22, 24-26, 28, 30). Only 2 reported a change in fat (23,31) or protein and CHO (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations